Performances of Crossbred Chickens Fed Fermented Papaya Leaf and Seed Powder at High Stocking Density - Sugiharto, S.; Yudiarti, T.; Widiastuti, E.; Wahyuni, H.; Sartono, T.; Pratama, A. R. (Tropical Animal Science Journal, 2021)
The study evaluated the influence of fermented papaya leaf and seed powder (FPLS) and/or multienzymes on the growth, physiology, antioxidant, and gut ecology of the Indonesian crossbred chicken (ICC) at high stocking density. Three hundred and seventy ICC were randomly allotted to LSD (chicks fed conventional feed at low stocking density), HSD (chicks fed conventional feed at high stocking density), HSD+mE (chicks fed conventional feed plus multienzyme at high stocking density), HSD+FPLS (chicks fed FPLS at high stocking density) and HSD+FPLS+mE (chicks fed FPLS plus multienzyme at high stocking density). Body weight and feed intake were determined weekly. Two ICC were taken from each pen (10 chicks per treatment group) at week 10 for sampling. The study was arranged based on a completely randomized design with five treatment groups, each consisted of five replicates. Except for performance, analysis of variance was conducted on two chicks from each replicate (10 chicks per treatment group). Chicks in LSD consumed more (p